Laura Crombie, Archery and Crossbow Guilds in Medieval Flanders 1300-1500 - J.A. (Hans) Mol (BMGN: Low Countries Historical Review, 2017)
Laura Crombie, Archery and Crossbow Guilds in Medieval Flanders 1300-1500 (Woodbridge: Boydell Press, 2016, 259 pp., ISBN 9781783271047).